(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
In the article, the essence of the concept of "Prosperous and safe neighborhood" in New Uzbekistan in recent years, the importance of the "Safe neighborhood" system in the self-management structure, problems of neighborhood residents’ preparation for such situations in emergency situations, prevention of crime in neighborhoods It aims to study the concept of "safe neighborhood". In conducting the research methods, the comparative and critical study of political and pedagogical literature on the problem, the methods of statistical data analysis were used. Results of the study Suggestions have been made regarding the implementation of the "Prosperous and safe neighborhood" system in the neighborhoods in our country.